Values in models of modernization - "Dutta, Ratna." (Delhi, 1971)
This book is emphasized on the value of Theoretical reasoning. Author has taken a major tradition of Western Sociology -- thge 'astion schema' isolated the number of conceptual ambiguities and vulnerabilities in its applicability to the modernization of the new nations, and suggested a number of theoretical perspective to supplement it.
Keywords: Sociology